Religious extremism versus extremes of desacralisation: rethinking the status of religious education - Hashi, Abdurezak Abdulahi (Research Association for Interdisciplinary Studies (RAIS), 2017)
Religion has been part and parcel of human history and heritage. It has served as a useful companion to man in the journey of intellectual growth,which has in most of the cases, helped humanity to answer, in various forms, the basic questions of life. Though religion has been a useful companion to man, yet religious thought has never been without challenges. There have been instances in which religion is challenged by strong tendencies of secularism and the process desacralisation of politics, ethics and values, in which traditional territories of religion in life are rolled back. On the contrary, religious extremism has been another challenge of religious life, in which violent act were committed in the name of religion. Modern proponents of extreme secularism have equated religion to infantile and childish expressions of man which functions as obstacle to the scientific mind of man, therefore they say in the age of science; religion should disappear once for all. However, contemporary religious extremists exhibit the behavior of imposing their religious thoughts violently; they do so by demonize other religious faiths as well as ideologies and philosophies other than their own, and thus feel justified to use violent behavior against those who hold different beliefs and ideas. The question is, other than denying “the value of religion in life” or “demonizing other faiths”, can there be other intellectual positions towards religion? This paper uses analytical method to address common trends of intellectual extremism for or against religious education; be it in the form of secular or religious thought. It re-examines the status of religious education in modern times, and the challenges posed by intellectual extremisms against the function and the role of religious education in life